How to train university professors in assessment? A systematic literature review - Beatrice Doria; Valentina Grion; Cristina Zaggia (Firenze University Press, 2024)
Educational research has recognized assessment as a crucial factor of university teaching, prompting Brown (2014) to consider that improving the quality of education requires a renewal of assessment practices. Such centrality suggests that university professors should adopt effective assessment practices. However, professors seem to exhibit forms of resistance to changing assessment practices, stemming from various reasons. Considering this, it would seem appropriate to develop training and research spaces specifically dedicated to assessment in the university context. This research, through a systematic literature review, aims to explore continuous training of university professors on assessment, to identify its peculiar characteristics and suggest guidelines for developing appropriate professional development initiatives. The results obtained may be of interest for designing effective assessment training programs and may also stimulate further research on the topic.   Come formare i docenti universitari alla valutazione? Una rassegna sistematica della letteratura. La ricerca educativa ha riconosciuto la valutazione come un elemento cruciale della didattica universitaria, tanto da indurre Brown (2014) a considerare che per migliorare la qualità dell'istruzione sia necessario un rinnovamento delle pratiche valutative. Tuttavia, i docenti sembrano attuare forme di resistenza al cambiamento delle pratiche valutative, con motivazioni di varia natura. Pertanto, sembrerebbe opportuno sviluppare spazi formativi e di ricerca dedicati specificamente alla formazione alla valutazione in ambito universitario. Questa ricerca, attraverso una rassegna sistematica della letteratura, si propone proprio di esplorare la formazione continua dei docenti alla valutazione, per identificarne le caratteristiche peculiari e suggerire linee guida per sviluppare apposite iniziative di sviluppo professionale. I risultati ottenuti possono costituire elementi d'interesse per la progettazione di percorsi formativi efficaci sulla valutazione, stimolando ulteriori ricerche sull'argomento.